1998
DOI: 10.1002/(sici)1098-2752(1998)18:3<192::aid-micr13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the improvement of sensibility after primary median nerve repair at the wrist

Abstract: In the Istanbul Hand Surgery and Microsurgery Centre, between 1991-1996, 28 out of 54 patients who had clean-cut median nerve laceration at the wrist level were evaluated in a detailed manner regarding the improvement of sensibility following primary repair. Semmes-Weinstein monofilament and vibration tests form the group of threshold tests, and static and dynamic two-point discrimination tests and the Moberg pick-up test form the group of functional tests which were applied to the patients. Follow-up was from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Some studies reported statistical significance only, and the strength of correlation or effect size cannot be assessed. 40 , 45 , 47 In contrast, there were correlations with moderate strength but statistically nonsignificant. 42 The nonsignificance may be because of small sample size, 42 and the results may still have clinical value.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Some studies reported statistical significance only, and the strength of correlation or effect size cannot be assessed. 40 , 45 , 47 In contrast, there were correlations with moderate strength but statistically nonsignificant. 42 The nonsignificance may be because of small sample size, 42 and the results may still have clinical value.…”
Section: Discussionmentioning
confidence: 81%
“… NA MRC sensory scales † Jaquet et al 14 RTW-yes/no Poor sensory recovery had an odds ratio of 2.94 for inability to return to work; 95% CI, 1.50–5.76; P =.002. Age, sex Selma et al 47 Moberg's pick-up Means of the pick-up performance between 2 groups (S3+, S4 vs S1, S2, S2+, S3) were different, P <.05, Mann-Whitney U . \ Vordemvenne et al 48 DASH In the 3-factor analysis, MRC sensory score and DASH both had meaningful loadings (0.863, 0.552) on the sensory factor.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations